Child second language development of English tense and aspect: The role of narrative organization. (13th July 2022) - Kang, Hyun-Sook; Uchikoshi, Yuuko
Abstract: Much research has documented that second language (L2) development of tense and aspect markers is influenced by a range of factors that include cross-linguistic influences, phonological nature of forms, inherent semantics of predicates, and discourse structure. Nonetheless, relatively little research has examined the role of discourse organization in the development of tense and aspect marking. To expand our understanding of L2 tense and aspect, this study examined child L2 development of English tense and aspect in oral narratives in relation to the foregrounding and backgrounding of narrative discourse. Thirty-eight learners' oral narratives were elicited, using Frog, Where Are You? (Mayer, 1969) three points in time: kindergarten, Grade 1, and Grade 2. The foreground in oral narratives was associated with more frequent use of the simple past than the background across the grade levels. While the occurrence of the simple past did not necessarily mark the foreground, the simple past emerged as the dominant form in the foreground in Grade 1. In the background, on the other hand, it took longer for the past forms to catch up with the non-past forms. The simple past became dominant in the background in Grade 2.